Level of Psychological Well-Being Among Prisoners - Nur Oktavia Hidayati; Toharudin Toharudin; Theresia Eriyani (Universitas Padjadjaran, 2021)
Changes in lifestyle by being required to be isolated result in more difficult to self and social adjustment for prisoner. Psychological well-being is a prosperous mental condition that allows a person to conduct a self-evaluation, while feelings of disappointment with the situation have an impact on psychological well-being, resulting in psychosocial problems. The purpose of this study was to describe the psychological well-being of prisoners. The research method using quantitative descriptive. This research was conducted in Lapas Klas IIB Garut, 90 prisoners were obtained by purposive sampling technique. The instruments used were Ryff's Psychological Well-Being Scales (RPWBS). Data were analyzed using descriptive statistics presented in the frequency distribution table. The results showed that in general the psychological well-being of prisoners were in the high category (58,9%). However, there are two dimensions which are included in the low category, namely the dimensions of self-acceptance and personal development. Therefore, the attention of nurses is needed by prisoners especially in psychological condition issue, which is expected to maintain and improve the psychological well-being of the prisoners.